Ulcerative Keratitis with Iris Prolapse in a Bitch: Ceratite ulcerativa com prolapso de íris em cão - Vieira Costa, Daniel; Vaz Lobo, Thaissa; França de Paula Orlando Goulart, Camila; Martins Oliveira, Iago (Acta Scientiae Veterinariae, 2024)
Background: Ulcerative keratitis is a condition that is classified based on the depth and exposure of the corneal layers and the clinical signs are epiphora, blepharospasm, photophobia, corneal opacity, conjunctival hyperemia and miosis. The diagnosis involves ophthalmological examination with dye eye drops, and the aim of treatment is to regenerate the cornea, prevent infection, control pain, and eliminate the cause. It may include surgery depending on the severity of the case. The aim of this manuscript is to report a clinical case of ulcerative keratitis progressing to iridocele in a bitch. Case: A 3-year-old unneutered bitch Shih Tzu was treated for a change in the surface of its cornea. During the consultation, it was possible to see decreased alertness, decreased response of the optic (II) and oculomotor (III) cranial nerve pairs, ciliary congestion, corneal edema, purulent ophthalmorrhea, iridocorneal synechia, and an intraocular pressure (IOP) of 10 mmHg. The 1% sodium fluorescein test confirmed the presence of ulcerative keratitis by staining the stromal region and there was prominent pigmented tissue in the center of the lesion, characterizing ocular perforation with iris prolapse. The case was treated as an ophthalmic emergency and surgery with a conjunctival pedicle graft in the right eye was the chosen treatment. The procedure began by obtaining a mobile conjunctival flap from the mid-dorsal bulbar conjunctiva, followed by excision of the prolapse trapped in the corneal wound. Subsequently, the iridocorneal synechia was undone with a surgical spatula and the iris was repositioned in the anterior chamber. The previously dissected conjunctiva was placed over the area of the ocular surface to be covered and sutured. Air was then injected into the previous chamber to reform it. Finally, to protect the cornea and reduce corneal exposure, temporary tarsorrhaphy was performed. At day 19 of follow-up, the conjunctival graft was firmly adhered to the area of the lesion and the sutures were almost completely absorbed. Moreover, there was a reduction in ciliary congestion, corneal edema, and active blood vessels in the cornea. In the tonometry test, the pressure was recorded at 12 mmHg. Discussion: Ulcerative keratitis occurs when rupture of the epithelial layer, resulting in exposure of the underlying corneal stroma. This lesion leads to clinical manifestations in dogs such as ophthalmorrhea, blepharospasm, photophobia, conjunctival hyperemia, corneal edema, and miosis. In the case presented here, the clinical signs were similar to those described in the literature as the most frequent in ulcerative keratitis. The occurrence of corneal perforations can result from the continuous progression of a corneal ulcer. In the case of a perforation, the aqueous humor escapes from the anterior chamber and the iris may accompany it, causing a prolapse consisting of pigmented tissue in the damaged area of the cornea. According to this premise, in this case, during the definitive diagnosis made with the use of dye eye drops, the injured right eye showed, in addition to the stained stroma, prominent pigmented tissue corresponding to the iris, which was trapped in the center of the corneal perforation. Conjunctival grafting is the gold standard approach to preserving corneal and ocular integrity, as it replaces lost corneal tissue and provides vascularization, because the cornea has no blood supply of its own. As described in the literature, in this case we opted for a graft obtained from the bulbar conjunctiva. The conjunctival flap obtained from the limbus region was fixed to the cornea using simple interrupted sutures. The graft was made in the area lateral and dorsal to the limbus, due to better traction and exposure of the bulbar conjunctiva, thereby allowing partial resection and displacement. Keywords: cornea, graft, eye, ocular trauma. Título: Ceratite ulcerativa com prolapso de íris em cadela Descritores: córnea, enxerto, olho, trauma ocular.